3D silicon doped hydroxyapatite scaffolds decorated with Elastin-like Recombinamers for bone regenerative medicine. (November 2016) - Vila, Mercedes; García, Ana; Girotti, Alessandra; Alonso, Matilde; Rodríguez-Cabello, Jose Carlos; González-Vázquez, Arlyng; Planell, Josep A.; Engel, Elisabeth; Buján, Julia; García-Honduvilla, Natalio; Vallet-Regí, María
Graphical abstract: Abstract: The current study reports on the manufacturing by rapid prototyping technique of three-dimensional (3D) scaffolds based on silicon substituted hydroxyapatite with Elastin-like Recombinamers (ELRs) functionalized surfaces. Silicon doped hydroxyapatite (Si-HA), with Ca10 (PO4 )5.7 (SiO4 )0.3 (OH)1.7 h0.3 nominal formula, was surface functionalized with two different types of polymers designed by genetic engineering: ELR-RGD that contain cell attachment specific sequences and ELR-SNA 15/RGD with both hydroxyapatite and cells domains that interact with the inorganic phase and with the cells, respectively. These hybrid materials were subjected to in vitro assays in order to clarify if the ELRs coating improved the well-known biocompatible and bone regeneration properties of calcium phosphates materials. The in vitro tests showed that there was a total and homogeneous colonization of the 3D scaffolds by Bone marrow Mesenchymal Stromal Cells (BMSCs). In addition, the BMSCs were viable and able to proliferate and differentiate into osteoblasts. Statement of Significance: Bone tissue engineering is an area of increasing interest because its main applications are directly related to the rising life expectancy of the population, which promotes higher rates of several bone pathologies, so innovative strategies are needed for bone tissue regeneration therapies. Here we use the rapid prototyping technology to allow moulding ceramic 3D scaffolds and we use different bio-polymers for the functionalization of their surfaces in order to enhance the biological response. Combining the ceramic material (silicon doped hydroxyapatite, Si-HA) and the Elastin like Recombinamers (ELRs) polymers with the presence of the integrin-mediate adhesion domain alone or in combination with SNA15 peptide that possess high affinity for hydroxyapatite, provided an improved Bone marrow Mesenchymal Stromal Cells (BMSCs) differentiation into osteoblastic linkage.